The Effect of Liquidity Ratio, Solvency Ratio, Profitability Ratio and Listing Age to Audit Delay of Insfratucture Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period - KOLEANGAN, Justy Nathaneil Pangkey; LAMBEY, Robert; KOPOJOS, Peter Marshall (PT Keberlanjutan Strategis Indonesia, 2022)
The financial statements of companies go public must be audited by independent auditors before being presented to the public. This process takes time which is called audit delay, audit delay is calculated from the closing date of the book until the date of the audit report. The deadline from the OJK is 90 days after closing the books. Late publication of financial reports has a negative impact on the company. This study aims to determine the effect of Liquidity Ratios, Solvency Ratios, Profitability Ratios, and Listing Age on Audit Delay in Infrastructure Sector Companies listed on the IDX. The research method used is quantitative. The population used is the Infrastructure Sector companies listed on the IDX. The sample used is Financial Statements that have been audited and published in Infrastructure Sector Companies Listed on the IDX for the 2018-2021 period of 47 samples. The Source of data used is secondary data. The analytical techniques used in this study include descriptive statistical analysis, outer models, inner models, and hypothesis testing with the SmartPLS3.0 program. The results of the study show that the Liquidity Ratio affects audit delay. Meanwhile, the Solvability Ratio, Profitability Ratio, and listing age do not affect audit delay